Young people’s well-being and the association with social capital, i.e. social networks, trust and reciprocity - Minna Tuominen; Leena Haanpää (INVEST Research Flagship, 2022)
The paper explores the association between the social capital of young people at 12-13 years and their subjective well-being using Finland’s sub-sample of the third wave of the International Survey of Children’s Well-Being. Despite many previous studies on this topic, relatively little is known of the actual effect of social capital given that different studies define and measure social capital differently. We rely strictly on Robert Putnam’s theory and understand it as a combination of social networks, trust, and norms of reciprocity. We measure well-being with two context-free scales: a one-dimensional overall life satisfaction scale and a five-dimensional Student’s life satisfaction scale. The analysis is done with linear and unconditional quantile regression. The results indicate that all three dimensions of social capital are significantly associated with well-being. Of the three, trust is the strongest predictor explaining over 30% of the variance in both well-being scales. Quantile regression suggests that while social capital is important for young people across the quantiles, trustful relations with family members are particularly important for those who fare poorly otherwise. For those who are satisfied with their lives, the importance of family members is lower, albeit still significant, but for them relationships with other people gain greater importance.